Sexually Transmitted Infections Surveillance in Pakistan - Sharaf Ali Shah; Arshad Altaf (Journal of the Pakistan Medical Association)
Sexually transmitted infections (STIs) are transferred fromperson to person by unsafe sexual contact. Some STIs canalso be transmitted through transfusion of unscreenedblood during pregnancy, childbirth, and breastfeeding.1